Augmented Regimes - Biasillo, Roberta (Journal for the History of Environment and Society, 2022)
Abstract This article combines environmental and political history approaches, and explores the relationship between the environment and the political with regard to regime-building processes. In doing so, it proposes a procedural and process-oriented approach to the analysis of Italian liberal and fascist regimes (1860s-1930s) from the perspective of environmental politics and management. Based on the empirical case of the Pontine Marshes, the article addresses the question of whether distinctive liberal and fascist features existed in relation to the environment and proposes three areas worthy of further investigation that bridge the distance between environmental and political history. The first of these areas being the decision-making process over the environment; the second, the systems of environmental knowledge production that a regime accepts and deploys in environmental management; the third, the principles behind environmental intervention or non-intervention.
Keywords: Italian fascism